Perbandingan Pembuatan Surat Izin Usaha Di Indonesia Dan Malaysia - Harefa, Mastiwi Putri; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
This study compares the process of making a business license in Indonesia and Malaysia with a focus on requirements, bureaucracy, regulations, use of technology, time and costs. Indonesia has a more complex process, high bureaucracy, longer time and higher costs than Malaysia. Despite this, both countries face similar challenges such as corruption and regulatory harmonization. Recommendations to increase efficiency and save power include simplifying procedures, regulatory reform, utilizing digital technology, increasing transparency, regional cooperation, and developing human resources. It is hoped that the implementation of these recommendations will improve the business licensing process, support economic growth, and promote regional economic integration in Southeast Asia.